Option Trading, Price Discovery, and Earnings News Dissemination* - AMIN, KAUSHIK I.; LEE, CHARLES M. C. (Contemporary Accounting Research, 1997)
Abstract. Option market activity increases by more than 10 percent in the four days before quarterly earnings announcements. We show that the direction of this preannouncement trading foreshadows subsequent earnings news. Specifically, we find option traders initiate a greater proportion of long (short) positions immediately before “good” (“bad”) earnings news. Midquote returns to active‐side option trades are positive during nonannouncement periods and are significantly higher immediately prior to earnings announcements. Bid‐ask spreads for options widen during the announcement period, but traders do not gravitate toward high delta contracts. Collectively, the evidence shows option traders participate generally in price discovery (the incorporation of private information in price), and more specifically in the dissemination of earnings news.